2020
DOI: 10.3390/su12083493
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Indigenous Food Crops in Africa and the Implications for more Sustainable and Healthy Food Systems

Abstract: Indigenous and traditional foods crops (ITFCs) have multiple uses within society, and most notably have an important role to play in the attempt to diversify the food in order to enhance food and nutrition security. However, research suggests that the benefits and value of indigenous foods within the South African and the African context have not been fully understood and synthesized. Their potential value to the African food system could be enhanced if their benefits were explored more comprehensively. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(168 citation statements)
references
References 106 publications
4
164
0
Order By: Relevance
“…Legumes are known to significantly contribute to the supply of bioactive compounds to the body due to their antioxidant activity, attributed to phenolic compounds, and are also rich sources of proteins, dietary fibres, and micronutrients. Legumes have also acquired a significant importance in African traditional medicine [42,43]. Our results revealed that Lablab purpureus, Phaseolus vulgaris and Vigna unguiculata have higher protein contents (~23%), with the former containing also high levels of phenolic contents and antioxidant capacities in its leaves, together with Cajanus cajan.…”
Section: Chemical Compositionmentioning
confidence: 72%
“…Legumes are known to significantly contribute to the supply of bioactive compounds to the body due to their antioxidant activity, attributed to phenolic compounds, and are also rich sources of proteins, dietary fibres, and micronutrients. Legumes have also acquired a significant importance in African traditional medicine [42,43]. Our results revealed that Lablab purpureus, Phaseolus vulgaris and Vigna unguiculata have higher protein contents (~23%), with the former containing also high levels of phenolic contents and antioxidant capacities in its leaves, together with Cajanus cajan.…”
Section: Chemical Compositionmentioning
confidence: 72%
“…In the past, these food plants have played an important role in the diet and traditional medicine of African communities ( Catarino et al, 2016 ; Havik et al, 2018 ; Akinola et al, 2020 ). Several of these species are important African crops ( Amadou et al, 2013 ; Tadele, 2016 ), but in Cabo Verde there are no evidences of their cultivation, most of them being used for livestock grazing ( Barbosa, 1961 ) or has building materials (e.g., thatching with I. cylindrica ).…”
Section: Discussionmentioning
confidence: 99%
“…The environment influences China's urbanization 14,000 Km 2 areas experienced a high concentration of CO2 emissions [85]. The rapid dimension in construction and renovation of space heating is obsessed with urbanization [86,87]. The higher intensity of CO2 emissions is recorded in the urban territories than residential or rural areas because of the higher volume of traffic and denser population [88,89].…”
Section: Urbanization and Ruralizationmentioning
confidence: 99%